2021
DOI: 10.3389/fpsyg.2021.723823
|View full text |Cite
|
Sign up to set email alerts
|

Romantic Attachment and Difficulties in Emotion Regulation on Dyadic Adjustment: A Comprehensive Literature Review

Abstract: In romantic relationships, individual differences are determinant factors for relational quality. Specifically, romantic attachment (RA) and difficulties in emotional regulation influence each other and may have predictive potential for the perceived dyadic adjustment (DA) level. This paper aims to identify the developmental parallel between behavioral patterns built since childhood and the construction of the emotional regulation skills that characterize them. Our analysis was based on the attachment theory a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 128 publications
(237 reference statements)
0
8
0
2
Order By: Relevance
“…Alternatively, it is possible that the communications by distance lead to more misunderstandings, therefore suffering more from negative emotions which resulted in an increase of the depression levels. All these results suggest that the university population that was in a romantic relationship should be given more consideration [32,33].…”
Section: Discussionmentioning
confidence: 89%
“…Alternatively, it is possible that the communications by distance lead to more misunderstandings, therefore suffering more from negative emotions which resulted in an increase of the depression levels. All these results suggest that the university population that was in a romantic relationship should be given more consideration [32,33].…”
Section: Discussionmentioning
confidence: 89%
“…The counterintuitive findings for sexual desire—one’s level of interest in sexual activity (Birnbaum, 2018)—can be interpreted in light of both the intimacy-interfering aspect of poor emotion regulation and the context-dependent function of sexual desire in relationships (Birnbaum, 2018). Because difficulties regulating negative emotion undermine moment-to-moment intimacy (i.e., the degree to which intimate partners feel close, connected, and bonded to each other; Fávero et al, 2021; Tani et al, 2015), individuals who struggle more to manage their negative feelings and behaviors during sexual conflict may feel less emotionally close with their partner: concurrently, they may report lower dyadic sexual desire. Indeed, the positive associations between intimacy and sexual desire appear to be stronger when these constructs are measured in closer proximity to each other (Shrier & Blood, 2016; van Lankveld et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This is conditioned by the peculiarity of the avoidant attachment style, namely, the tendency of respondents to be guided by reason rather than feelings, the fear of falling into the trap of relationships, the value of freedom, and ease in love. M. Favero found that people with avoidant attachment style are characterised by emotional deactivation to suppress negative emotions caused by the fear of rejection [23]. A. Santona found that people with the anxious type, on the contrary, show increased emotional responses [24].…”
Section: Level Of Reliability Of Attachmentmentioning
confidence: 99%